2014
DOI: 10.5935/1678-9741.20140031
|View full text |Cite
|
Sign up to set email alerts
|

Left Subclavian Artery Stenting: an option for the treatment of the Coronary-Subclavian Steal Syndrome

Abstract: Introduction The subclavian steal syndrome is characterized by the vertebral artery flow inversion, due to a stenotic lesion in the origin of the subclavian artery. The Coronary-subclavian Steal Syndrome is a variation of the Subclavian Steal Syndrome and is characterized by inversion of flow in the Internal Thracic artery that has been used as conduct in a myocardial revascularization. Its diagnosis must be suspected in patients with difference in pulse and arterial pressure in the upper limbs, that present w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…Severe stenosis (≥70%) often caused stable or unstable angina or even myocardial infarction, whereas unstable angina or myocardial infarction were more frequent among occluded lesions because severe SAS compromised or even reversed the flow of IMA. Previous studies have shown that the symptomatic remission rate after the release of brachiocephalic and subclavian arterial stenosis fluctuates between 90% and 100% . The actuarial remission rate of 94.6% for subclavian artery stenting in this study reflected the effectiveness of this practice.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Severe stenosis (≥70%) often caused stable or unstable angina or even myocardial infarction, whereas unstable angina or myocardial infarction were more frequent among occluded lesions because severe SAS compromised or even reversed the flow of IMA. Previous studies have shown that the symptomatic remission rate after the release of brachiocephalic and subclavian arterial stenosis fluctuates between 90% and 100% . The actuarial remission rate of 94.6% for subclavian artery stenting in this study reflected the effectiveness of this practice.…”
Section: Discussionsupporting
confidence: 67%
“…Overall, the incidence of CSSS was estimated to be 0.2–3.4% for patients with IMA‐CABG. Some case reports and small series have shown the feasibility of endovascular therapy of SAS for CSSS . However, due to small sample sizes and the short follow‐up durations of these studies, further exploration and evaluation were needed.…”
Section: Introductionmentioning
confidence: 99%
“…Endovascular treatment is the preferred procedure for treating vascular diseases such as dysfunctional arteriovenous fistula and steno-occlusive subclavian artery disease, and bleeding or tumor embolization [13][14][15][16][17][18]. The technical success or safety of the endovascular procedure has been sufficiently discussed in various fields [19][20][21]. Therefore, further interest has focused on the convenience of patients undergoing procedure rather than on its performance.…”
Section: Discussionmentioning
confidence: 99%
“…However, proximal lesions are not infrequent. When left subclavian artery stenosis is present (up to 2% of patients undergoing coronary surgery) [ 34 ], the internal mammary artery flow can be jeopardized, and endovascular stenting may be indicated prior to arterial grafting [ 34 ]. In other cases, with proximal upper limb artery obstruction ( Figure 2(a) ), RA usage is not advised.…”
Section: When Not To Use the Radial Artery?mentioning
confidence: 99%
“…Angiographic radial artery stenosis was detected in 1.7% of cases in one study [ 35 ]. Among patients requiring coronary bypass grafting, the incidence of macroscopic RA calcification is approximately 6% [ 33 , 34 ]. The ulnar artery is then usually calcified as well.…”
Section: When Not To Use the Radial Artery?mentioning
confidence: 99%